2006
DOI: 10.1080/09500340600674291
|View full text |Cite
|
Sign up to set email alerts
|

Scheme for generating entangled states of two field modes in a cavity

Abstract: This paper considers a two-level atom interacting with two cavity modes with equal frequencies. Applying a unitary transformation, the system reduces to the analytically solvable Jaynes-Cummings model. For some particular field states, coherent and squeezed states, the transformation between the two bare basis's, related by the unitary transformation, becomes particularly simple. It is shown how to generate, the highly non-classical, entangled coherent states of the two modes, both in the zero and large detuni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In the large detuning regime, g  †Â , we impose an adiabatic approximation [33] to find, up to some trivial constants,…”
Section: Intrinsic Photonic Josephson Effect In a Bimodal Resonatormentioning
confidence: 99%
“…In the large detuning regime, g  †Â , we impose an adiabatic approximation [33] to find, up to some trivial constants,…”
Section: Intrinsic Photonic Josephson Effect In a Bimodal Resonatormentioning
confidence: 99%
“…033606-2 being coherent with an amplitude determined by the balancing of losses κ and pumping η. The cavity is taken to couple dispersively to the atoms, and the excited atomic state can hence be eliminated adiabatically [22]. In a frame rotating with the pump frequency ω p and assuming ultracold atoms, the Hamiltonian reads [15] …”
Section: A Cavity-mediated Double-well For Cold Atomsmentioning
confidence: 99%
“…[12,13], as well. Recently, many researchers have been regarded the JCM as a source of the entanglement [14,15,16,17,18,19,20,21,22,23].…”
Section: Entanglement Between the Atom And The Thermal Fieldmentioning
confidence: 99%
“…In Ref. [16], an atom interacting with two cavity modes is considered and it is shown that this system can be reduced to the JCM. Using this system, generation of entangled coherent states is discussed.…”
Section: Introductionmentioning
confidence: 99%